Pengaruh Harga dan Kualitas Produk Smartphone Iphone terhadap Keputusan Pembelian Konsumen - Armika Intan R Berutu; Nursiah Fitri; Mardhiatul Husna; Aulia Benazira; Jamardua Haro (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The increasing increase in technology from year to year is a phenomenon in this research, one of which is the iPhone brand mobile device. The popularity of the iPhone smartphone is because the product is popular and is always available in every urban and inland area. This research aims to analyze the influence of price and product quality on the decision to purchase an iPhone smartphone at the Medan State Polytechnic, especially the Department of Business Administration. Sample selection used the non-probability sampling method, namely incidental sampling technique. The data collection technique was carried out through a questionnaire distributed to 93 respondents who were iPhone smartphone customers. The analytical method used is multiple linear regression with hypothesis testing using the SPSS version 27 program. The research results show that simultaneously price (X1) and product quality (X2) have a positive and significant effect on consumers' purchasing decisions (Y). The research results from the coefficient of determination test (R2) show that the variables Price and Product Quality are able to explain 40.5%, meaning that Price and Product Quality contribute or contribute to the decision to purchase an iPhone smartphone while the remaining 59.5% is influenced by other factors. outside this research.